2001
DOI: 10.1002/j.1939-4640.2001.tb03435.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibins in the Male Göttingen Miniature Pig: Leydig Cells Are the Predominant Source of Inhibin B

Abstract: ABSTRACT:The expression of inhibin subunits in the testes of the Göttingen miniature pig was examined by in situ hybridization and immunohistochemistry. In addition, the major forms were determined by enzyme-linked immunosorbent assay (ELISA). Strong positive immunostaining for the inhibin ␣ subunit was observed in Sertoli and late-stage germ cells, but it was weak in Leydig cells. However, Leydig cells showed strong positive staining for the ␤A subunit, but Sertoli cells and spermatogonia showed a weak reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…The quality of fractionated cells was verified by determining the expression of HSD3B (HSDB1), PRM1, and INHA, which are expressed specifically by Leydig cells (Raeside & Renaud 1983, Chemes et al 1992, germ cells (Domenjoud et al 1991), and both Sertoli and Leydig cells (Jin et al 2001) respectively. The fractionated testicular cells were frozen and stored in liquid nitrogen.…”
Section: Fractionation Of Testicular Cellsmentioning
confidence: 99%
“…The quality of fractionated cells was verified by determining the expression of HSD3B (HSDB1), PRM1, and INHA, which are expressed specifically by Leydig cells (Raeside & Renaud 1983, Chemes et al 1992, germ cells (Domenjoud et al 1991), and both Sertoli and Leydig cells (Jin et al 2001) respectively. The fractionated testicular cells were frozen and stored in liquid nitrogen.…”
Section: Fractionation Of Testicular Cellsmentioning
confidence: 99%
“…The fractionated testicular cells were snap frozen and stored in liquid nitrogen for extraction of RNA. The quality of cellular fractionation was verified by detecting 3-b hydroxysteroid dehydrogenase (HSD3B), protamine 1 (PRM1) and inhibin a (INHA) gene expression, which are specifically expressed by Leydig cells (Raeside & Renaud 1983, Chemes et al 1992, germ cells (Domenjoud et al 1991) and both Sertoli and Leydig cells ( Jin et al 2001) respectively.…”
Section: Fractionation Of Testicular Cellsmentioning
confidence: 99%
“…3A). The purity of these fractionated cells was also verified by determining the expression of HSD3B, PRM1 and INHA, which are expressed specifically by Leydig cells (Chemes et al 1992), germ cells (Domenjoud et al 1991) and both Sertoli and Leydig cells ( Jin et al 2001) respectively. Fractionation was shown to be quite satisfactory, i.e.…”
Section: Cellular Expression Of Rln and Rxfp1 Genes In The Boar Testismentioning
confidence: 99%
“…In the stallion, golden hamster and dog, the inhibin α, β A and β B subunits are present in both Sertoli and Leydig cells [10,16,24], and in adult monkeys, all three subunits are localized predominantly in Sertoli cells [8,36]. Previous studies showed that inhibin B is the major form of inhibins secreted from testes in men, Japanese macaques and Gottingen miniature pigs [7][8][9], but in the ram, inhibin A, and not inhibin B, was produced in testicular tissues [15]. In the present study, inhibin  and inhibin ( A and  B ) subunits were both expressed in testicular and scented glandular tissues, clearly indicating that apart from testicular tissues, the scented gland was an important source of inhibins in the muskrats.…”
mentioning
confidence: 99%